Variation among arthropod taxa in the amino acid content of exoskeleton and digestible tissue - Jamie T. Reeves; Colton Herzog; Cody L. Barnes; Craig A. Davis; Samuel D. Fuhlendorf; Shawn M. Wilder (Ecology and Evolution)
Abstract Arthropod consumption provides amino acids to invertebrates and vertebrates alike, but not all amino acids in arthropods may be digestible as some are bound in the exoskeleton. Consumers may not be able to digest exoskeleton in significant amounts or avoid it entirely (e.g., extraoral digestion). Hence, measures that do not separate digestible amino acids from those in exoskeleton may not accurately represent the amino acids available to consumers. Additionally, arthropods are taxonomically diverse, and it remains unclear if taxonomic differences also reflect differences in amino acid availability. Thus, we tested: (1) if there were consistent differences in the content and balance of amino acids between the digestible tissue and exoskeleton of arthropods and (2) if arthropod Orders differ in amino acid content and balance. We measured the amino acid content (mg/100 mg dry mass) and balance (mg/100 mg protein) of whole bodies and exoskeleton of a variety of arthropods using acid hydrolysis. Overall, there was higher amino acid content in digestible tissue. There were also significant differences in the amino acid balance of proteins in digestible tissue and exoskeleton. Amino acid content and balance also varied among Orders; digestible tissues of Hemiptera contained more of some essential amino acids than other Orders. These results demonstrate that arthropod taxa vary in amino acid content, which could have implications for prey choice by insectivores. In addition, exoskeleton and digestible tissue content differ in arthropods, which means that whole body amino acid content of an arthropod is not necessarily a predictor of amino acid intake of a predator that feeds on that arthropod.